Management Strategy in Developing the Halal Industry in the Era of Globalization - Kalimah, Siti (Indonesian Journal of Islamic Economics and Finance, 2023)
The halal industry has grown rapidly, becoming an important sector in the global market with a scope that includes food, pharmaceutical, cosmetic, and tourism products. This creates opportunities and challenges, especially in maintaining the authenticity and quality of halal products throughout the supply chain. This article aims to examine management strategies in the halal industry that are from the perspective of Islamic economics with materials consisting of halal ingredients, both substances, how to obtain and process them, and are carried out in the halal industry area, where all industrial lots must be allocated for halal products, have halal facilities and infrastructure, and have a halal management team and analyze the various challenges faced, and identify opportunities that can support the development of this sector. The research method used is a literature study of 20 recent journal articles on halal industry management by collecting relevant journal articles from various sources. The study results show that certification, technological innovation, and halal supply chains are important components that must be optimized. Thus, a comprehensive management approach is needed to sustain the halal industry's growth.